Implementation of Deep Learning and Gamification to Increase Student Learning Engagement - Amru Almu’tasim; Nining Khurrotul Aini (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study aims to address the problem of low student engagement at MTs Negeri 3 Sidoarjo, East Java, by integrating deep learning and gamification into a digital learning platform. Low student engagement at MTs Negeri 3 Sidoarjo, East Java, is often caused by impersonal teaching methods and the lack of interactive elements that suit their psychological characteristics. Therefore, this study proposes an adaptive system that utilizes deep learning to analyze individual student learning patterns and then uses it to personalize gamification content and challenges. This study used a mixed-methods experimental design involving two groups: an experimental group using an integrated learning platform and a control group using conventional learning methods. Quantitative data were collected through user activity logs (interaction duration, task completion rate), student engagement questionnaire scores, and academic grades before and after the intervention. The results showed that the learning platform integrating deep learning and gamification significantly increased student engagement (p < 0.05). Quantitative data showed an increase in the average interaction duration and task completion rate in the experimental group compared to the control group. Furthermore, there was a positive correlation between the level of engagement and students' academic scores in the experimental group. Interviews confirmed that students felt more motivated and enjoyed the learning process due to the challenging elements and personalized feedback provided by the platform. Overall, this study demonstrates that the combination of deep learning and gamification technology is an effective approach to improving student engagement and learning outcomes at MTs Negeri 3 Sidoarjo, East Java.